Free radical production by femtosecond laser lens irradiation in porcine eyes. Issue 8 (August 2019) - Masuda, Yoichiro; Igarashi, Tsutomu; Oki, Kotaro; Kobayashi, Maika; Takahashi, Hiroshi; Nakano, Tadashi
Abstract : Purpose : To investigate the relationship between the generation of free radicals and femtosecond laser lens irradiation. Setting : AMO Laboratory, Tokyo, Japan. Design : Ex vivo studies. Methods : Hydroxyphenyl fluorescein (HPF) was injected into the anterior chamber of fresh 6‐month‐old porcine cadaver eyes (N = 31). After laser irradiation, a plate reader was used to measure the fluorescence of the aqueous humor samples. Relative fluorescence units (RFU) were calculated by subtracting the average control value from the measured values of all the samples. Experiment 1: After determining the RFU in the 7 laser‐irradiated eyes, the relationship with the amount of laser energy was then assessed. Experiment 2: To clarify the issue regarding the degree of attenuation of the fluorescence intensity, HPF was simultaneously injected into 2 eyes, with 1 eye irradiated and the other eye used as a control. After dividing the RFU of the laser‐irradiated eye by the control RFU, the laser irradiation–control RFU ratio was calculated, and the relationship with the laser irradiation energy amount then assessed. Results : There was a significant correlation between the femtosecond laser lens irradiation energy and the RFU in the aqueous humor ( P < .05, analysis of variance). Conclusions : Femtosecond laser lens irradiation increases the quantity of free radicals in the aqueous humor, with the extent of the increase dependent on the amount of laser energy. These results suggest that excessive laser irradiation during femtosecond laser–assisted cataract surgery might cause corneal endothelial damage because of the free radicals created during the procedure.